Chemical and Functional Characteristics of Strawberry Tree (Arbutus unedo L.) Honey from Western Greece - Chrysoula Tananaki; Dimitrios Kanelis; Vasilios Liolios; Maria Anna Rodopoulou; Fotini Papadopoulou (Foods)
Strawberry tree honey (Arbutus unedo L.) is a rare monofloral honey type with unique characteristics, mainly produced in the Mediterranean region. Despite its distinct qualities, limited research on its physicochemical and biological properties, coupled with the absence of specific legislative standards, hinder its market potential. For this reason, in the present study, we analyzed strawberry tree honey samples collected from beekeepers in Western Greece, focusing on physicochemical properties (moisture, electrical conductivity, HMF, diastase activity, color, pH, acidity), total phenolic content, antioxidant activity, carbohydrate composition, and phenolic compounds profile. The results revealed high moisture content (19.2 ± 1.9%) and electrical conductivity (0.784 ± 0.132 mS cm−1), low diastase activity (9.6 ± 3.8 DN), and a strong crystallization tendency (1.01). Additionally, the honey exhibited elevated levels of total phenolic content (1169.9 ± 323.8 mg GAE kg−1 honey) and total antioxidant activity (10.98 ± 2.42 mmol Fe2+ kg−1 honey), compared to other blossom honeys, with homogentisic acid emerging as the dominant phenolic compound. These findings highlight the potential of strawberry tree honey as a high-value product, contributing to its enhanced market promotion.